Uji Kualitas Produk Pupuk Organik Beragensia Hayati - Mujiyo Mujiyo; Aktavia Herawati; Ganjar Herdiansyah; Suntoro Suntoro; Jauhari Syamsiyah; Widyatmani Sih Dewi; Hery Widijanto; Rahayu Rahayu; Sutarno Sutarno (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2022)
Processing cow dung into organic fertilizer with additional biological agents is an effort to prevent environmental pollution due to agricultural waste. Sources of organic fertilizer materials have different nutrient content. Good quality organic fertilizer means that it has match the Organic Fertilizer Standards based on the Decree of Agriculture Minister Republic Indonesia Number 261/KPTS/SR.310/M/4/2019. This activity aims to determine the quality of the bio-agent organic fertilizer product produced by Perkumpulan Pertanian Organik Wonoagung Wonogiri (PPOWW) by analyzing its nutrient content. The activities carried out include an initial survey of partner conditions, preparation of materials, and analysis of fertilizers. The results show that the PPOWW management understands the mechanism of standard and how to carry out quality control on the organic fertilizers produced. The results of the analysis of the nutrient content of PPOWW organic fertilizer products are N-total 1.32%, P2O5 1.50%, K2O 2.24%, C-organic 23.09%, C/N ratio 17.55 and pH 8.27 which have met the quality standards of organic fertilizers and biological fertilizers. The addition of biological agents in the process of making organic fertilizers is proven to improve the quality of fertilizers.